(untitled) (Damascus University Journal of Historical Studies, 2025)
The research attempts here to put an objective evaluation and judgment on the role of Dubis bin Sadaqa, who paid with his life as a price for the volatility of his loyalty at an important stage intertwined with events and political developments in Iraq. The Arab Emir Dubis bin Sadaqa al-Mazydi was described as a "wandering knight" who had a prominent role and imprint in deepening the conflict between members of the Seljuk family at an important stage of Arab and Islamic history during the sixth century AH / twelfth century AD. The Mazidi emirate in Hilla, during the reign of Dubis bin Sadaqa, turned into a center of Arab resistance against Seljuk control in light of the recovery of the Abbasid Caliphate and its quest for liberation from this control. The research deals with Dabees’ quest and his political ambition to expand his influence and establish his emirate’s position not only in the Middle Euphrates region, but also between forces with conflicting political ambitions on the political scene in Iraq, and to show his war actions directed against the Seljuk Sultanate, and to clarify his motives for these moves, and the results he reaped and the disclosure of his use of all means to reach his political ambition.